2018
DOI: 10.1080/02646838.2018.1443322
|View full text |Cite
|
Sign up to set email alerts
|

Construct and content validity of the Turkish Birth Satisfaction Scale – Revised (T-BSS-R)

Abstract: Data analysis determined that the T-BSS-R is a valid and reliable instrument to measure birth satisfaction in a population of Turkish women. The T-BSS-R is available for use from c.hollinsmartin@napier.ac.uk .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Using the BSS-R scale, mean birth satisfaction score in this study (23.8, SD 6.5) was lower than that in most studies in other countries such as US (32.4, SD 6.4) [ 31 ], Australia (30.4, SD 5.9) [ 34 ], UK (28.4, SD 5.6) [ 29 ], Spain (28.1, SD 6.2) [ 36 ], and Greece (27.4, SD 6.2) [ 32 ] but was higher than that in Turkey (20.4, SD 6.0) [ 33 ]. The high medicalized birth management in Iran may be an important reason for the lower birth satisfaction in the study setting compared to many of the other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the BSS-R scale, mean birth satisfaction score in this study (23.8, SD 6.5) was lower than that in most studies in other countries such as US (32.4, SD 6.4) [ 31 ], Australia (30.4, SD 5.9) [ 34 ], UK (28.4, SD 5.6) [ 29 ], Spain (28.1, SD 6.2) [ 36 ], and Greece (27.4, SD 6.2) [ 32 ] but was higher than that in Turkey (20.4, SD 6.0) [ 33 ]. The high medicalized birth management in Iran may be an important reason for the lower birth satisfaction in the study setting compared to many of the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Original version of the scale was developed in the UK in 2014 [ 29 ]. It is now internationally considered the instrument of choice for assessing birth satisfaction [ 30 ] and various versions of it have been validated, including the US-BSS-R [ 31 ], Greek-BSS-R [ 32 ], Turkish-BSS-R [ 33 ], Australian-BSS-R [ 34 ], Italian-BSS-R [ 35 ], and Spanish-BSS-R [ 36 ]. The two subscales (satisfaction with doctor and nurse-midwife, items 17–33) of the Mackey childbirth satisfaction rating scale [ 37 ] was used to measure staff support.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the tri-dimensional measurement model of the BSS-R (Objective 1) was conducted using Confirmatory Factor Analysis (CFA; (Brown, 2015)). CFA represents the statistical approach to evaluate a measurement model and has been applied to several BSS-R validation studies (Barbosa-Leiker et al, 2015;Göncü Serhatlıoğlu et al, 2018;Jefford et al, 2018;Vardavaki et al, 2015). The bi-factor model was also evaluated using CFA.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…The results of the present study demonstrated no significant correlations between maternal age and the Iranian-BSS-R total and subscale scores, which confirmed the divergent validity of the scale. In all the previous validation studies on the BSS-R, divergent validity has been confirmed (Barbosa-Leiker et al, 2015;Goncu Serhatlioglu et al, 2018;Martin & Martin, 2014;Romero-Gonzalez et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…In addition, such tools could help compare maternal satisfaction with natural delivery and cesarean section on a national scale. In Iran, the importance of these tools is further emphasized due to the high rate of cesarean section (Gibbons et al, 2010) and increased maternal request for cesarean section without medical indications (Darsareh et al, 2017). As such, the reduction of cesarean section is a priority of the Iranian Ministry of Health.…”
Section: Postpartum Iranian Womenmentioning
confidence: 99%